Selected problems of holistic management of the natural environment with the concept of sustainable development, as the basis for the establishment of a scientific environmental protection discipline - Jan Sandner (Studia Ecologiae et Bioethicae)
The article addresses a very important issue, being the lack of a specific environmental protection scientific discipline in Poland. The actual situation in this extent is analyzed and compared to the solutions of the EU based on the systematic basis accepted by the OECD. The author presents methodological solutions in his study, which may serve as the basis for the creation of a substantive framework for the designation of a separate environmental protection scientific discipline. These assumptions are supported by holistic elements, which are essential to environmental management with regard to the concept of sustainable development.